2015
DOI: 10.3390/nu7105431
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Parenting Practices on Eating Behaviors of Early Adolescents during Independent Eating Occasions: Implications for Obesity Prevention

Abstract: Among early adolescents (10–14 years), poor diet quality along with physical inactivity can contribute to an increased risk of obesity and associated biomarkers for chronic disease. Approximately one-third of United States (USA) children in this age group are overweight or obese. Therefore, attention to factors affecting dietary intake as one of the primary contributors to obesity is important. Early adolescents consume foods and beverages during eating occasions that occur with and without parental supervisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 147 publications
(176 reference statements)
4
95
2
3
Order By: Relevance
“…In the final model of this study, it was shown that family has a direct effect on overeating and has indirect effect on mediation of inhibition of intake on overeating. This finding is consistent with some of the previous findings [11][12][13][14][15][16][17][18][19][20]. A possible explanation is that when family does not evaluate the appearance of an individual as appropriate, they start to put pressure for slimming on the individual.…”
Section: Discussionsupporting
confidence: 92%
“…In the final model of this study, it was shown that family has a direct effect on overeating and has indirect effect on mediation of inhibition of intake on overeating. This finding is consistent with some of the previous findings [11][12][13][14][15][16][17][18][19][20]. A possible explanation is that when family does not evaluate the appearance of an individual as appropriate, they start to put pressure for slimming on the individual.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of age, those aged 12-19 years were more likely to be overweight or obese than those aged 2-5 and 6-11 years (20). In one study, the prevalence of obesity in those aged 11-18 years was reported as 7.7% (8.4% for females and 7% for males) (21). In that study, time watching TV or using computers>2h per day and the presence of obese persons in the family were found to be the risk factors responsible for obesity development.…”
Section: Discussionmentioning
confidence: 85%
“…Note that this new food mode is based on fast-foud or this type of food is harmful for health [16,17]. So, as we saw earlier in the survey, some students could adopt a diet that tends to be unbalanced without really being aware of it; it is primarily for this reason that we believe it is essential to create information for students.…”
Section: Meals and Structurementioning
confidence: 92%